Utilization of manual calculation media in realistic mathematics education to increase students' learning motivation - Jupriyanto, Jupriyanto; Ulia, Nuhyal; Sari, Yunita; Yustiana, Sari; Robiatusofiyah, Robiatusofiyah (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2024)
This research focuses on the influence of learning models; the study's main aim is to determine whether a realistic mathematical education learning model using manual calculation media can influence the motivation of class I students at SDN Temuroso 03. The research method used was a quantitative experimental type, a Pre-Experimental Design with One Group Pretest-Posttest type, and a saturated sample technique of 20 students. Data analysis techniques use prerequisite tests and condition tests. The SPSS research produced results, namely that the data was normally distributed, and the t-test calculations produced that Lower and Upper had negative values or sig (2-tailed) < a, so H0 was rejected, and H1 was accepted. Then, it was strengthened by the gain test results, which showed an increase in the average value of 0.47. So, it can be said that the Realistic Mathematic Education learning model using manual calculation media can influence and increase student motivation.